Evidence for differential localization of noradrenaline and neuropeptide Y in neuronal storage vesicles isolated from rat vas deferens - Fried, G (J Neurosci, 1985)
Using the technique of homogenization and subsequent density gradient centrifugation combined with ultrastructural analysis, the subcellular localization of noradrenaline and neuropeptide Y (NPY) was studied in vas deferens of castrated male rats. Noradrenaline showed two peaks in the gradient: one major peak at low density and another at high density. Only one NPY peak was seen, which coincided with the high density peak of noradrenaline. Electron microscopic analysis revealed high proportions of small and large vesicles in the light and heavy fractions, respectively. The present results indicate a differential subcellular localization of noradrenaline and NPY in the noradrenergic nerve endings of vas deferens. Thus, small vesicles seem to contain only noradrenaline, whereas the large vesicles may contain both noradrenaline and NPY.